Age and growth studies of hake (Merluccius merluccius L.) from ICES Divisions VIIIc and IXa - Iglesias-Martínez, Sergio; Dery, L. (International Council for the Exploration of the Sea (ICES), 1981)
The present work is done on 801 hake otoliths originating from Divisions VIIIc and IXa. Preliminary results concerning the existence of false rings anterior to the first Winter ring are found. This is the way that they are defined: larval zone, pelagic ring, recruitment ring and summer ring (table 1). At the same time a study is made about the edge formation in relation to the season of the year (table 2). Based on the agreements of these two authors a key length-age for 1979 (table 3) is presented. Also three equations of growth of males, females and both combined sexes are given. Le present travail a été fait avec 801 otolithes du merlu provenant des Divisions VIIIc et IXa. Résultats preliminaries concernant d'existence des fauses anneaux anterierures au premier anneau d'hiver ont été rencontrés. Ainsi on define: zone larvaire, anneau pelagique, anneau de recrutement et anneau d'été (Table 1). Au meme temp une étude sur la formation du bordure en relation avec la saison de l'an (Table 2) a été faite. Basés dans les accords des deux auteurs on presente une clé taille/âge pour 1.979 (Table 3). Ausi on donne trois équations de croissance pour males, femelles et pour les deux sexes combinés.